Pearls and Blackbirds; Healing Dark History - Giambazi, Kelsey (Self-Published, 2019)
Pearls and Blackbirds imbues over-due acknowledgement of the collective histories of trauma and sorrow of women from different cultures who faced unjust violence, dis-possession and agonising distress in the duty of State building Australia during the early days of the Pearling Industry.